Chemical Investigation of the Indonesian Tunicate Polycarpa aurata and Evaluation of the Effects Against Schistosoma mansoni of the Novel Alkaloids Polyaurines A and B - Casertano, Marcello (Mar Drugs, 2019)
A deep study of the metabolic content of the tunicate Polycarpa aurata, collected from Indonesian coast, afforded the isolation of two novel alkaloids, polyaurines A (1) and B (2), along with two new p-substituted benzoyl derivatives (3 and 4) and four known compounds (5–8). The structural elucidation of the new secondary metabolites was assigned by 1D, 2D NMR, and HRESIMS techniques. Computational studies resulted a useful tool to unambiguously determine in polyaurine B the presence of rarely found 1,2,4-thiadiazole ring. The effects of polyaurines A and B on mammalian cells growth and on the viability of different blood-dwelling Schistosoma mansoni (phylum: Platyhelminthes) stages, as well as egg production, were evaluated. Both compounds resulted not cytotoxic; interestingly some of the eggs produced by polyaurine A-treated adult pairs in vitro are smaller, deformed, and/or fragmented; therefore, polyaurine A could represent an interesting bioactive natural molecule to be further investigated.